Purification of Aspergillus sp. S1-13 chitinases and their role in saccharification of chitin in mash of solid-state culture with shellfish waste - Rattanakit N. (2014)
In a suspension of solid-state culture of Aspergillus sp. S1-13 containing a lactic acid-treated crab shell as the substrate, the saccharification of chitin in the shell proceeded to form N-acetylglucosamine (GlcNAc): the culture was the source of chitin and chitinases. The analysis of chitinases in the water-extract of the solid-state culture indicated occurrence of an exochitinase (Exo, MW 73 kDa) and two endochitinases. The amounts of the endochitinases suggested that one of them (Endo-1, MW 45 kDa) might be the main species in the chitin-saccharification. The amount of GlcNAc released from the LA-treated crab shell by the combined action of isolated Exo and Endo-1 was very small, predicting participation in the saccharification of other enzyme species, which might be hardly extracted with water from the solid-state culture. The re-extraction of the solid-state culture using 2 M KCl, which was extracted with water beforehand, demonstrated another endochitinase (Endo-2, MW 51 kDa). Endo-2 isolated from the salt-extract can adsorb to chitin, and can hydrolyze the chitin in the adsorbed state. The roles of these chitinases in the chitin-saccharification based on their properties and combined action were discussed. © 2007 The Society for Biotechnology, Japan.